The Construction of Identity and Solidarity in Arabic Language Content About Palestine on the Instagram Account 'Ayn 'Ala Filastin: A Sociolinguistic Study - Fatimatuzzahra Nasution; Nur Fadillah; Nursukma Suri (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the construction of identity and solidarity in Arabic-language Instagram content related to Palestine from a sociolinguistic perspective. Social media has become a crucial space for expressing collective identity and mobilizing global solidarity. This research employs a qualitative approach using discourse analysis to investigate linguistic strategies in digital communication. The data consist of 15 selected Arabic captions from the Instagram account عين على فلسطين posted between January and March 2025. The analysis is based on the identity construction framework of Bucholtz and Hall (2005) and Critical Discourse Analysis by Fairclough (2015). The findings reveal that identity and solidarity are constructed through collective pronouns, emotional metaphors, and resistance-oriented expressions. These linguistic strategies not only reflect ideological positions but also strengthen emotional engagement and digital solidarity among audiences.